Bilateral Kidney Infarction Due to Primary AL Amyloidosis: A First Case Report. Issue 17 (May 2015) - Mihout, Fabrice; Joseph, Laure; Brocheriou, Isabelle; Leblond, Véronique; Varnous, Shaïda; Ronco, Pierre; Plaisier, Emmanuelle
Abstract : Abstract: Primary Amyloid Light-chain (AL) amyloidosis is a rare form of plasma cell dyscrasia characterized by tissue deposition of monoclonal immunoglobulin light chain. Kidney involvement is the most frequent manifestation, and patients usually present with glomerular disease. We report an exceptional case of bilateral kidney infarcts caused by AL amyloidosis. A 34-years-old man presented with progressive dyspnea, loin pain, recurrent macroscopic hematuria, and acute kidney injury. Computed tomography showed bilateral kidney infarcts. The diagnosis of AL amyloidosis was established on the kidney biopsy with the characterization of major vascular amyloid deposits that selectively stained with antilambda light chain antibody. An amyloid restrictive cardiomyopathy was also present, responsible for the life-threatening conduction disturbance, but without patent cardioembolic disease. The patient then underwent emergency heart transplantation, followed by a conventional chemotherapy with bortezomib, melphalan, and dexamethasone. More than 3 years later, the patient has subnormal renal function, a well-functioning heart transplant, and a sustained hematologic response. In addition to the very uncommon presentation, this case illustrates the tremendous progress that has occurred in the management of severe forms of AL amyloidosis.